Combinatorial therapies for spinal cord injury: strategies to induce regeneration - Gomes, Eduardo Domingos Correia (2019)
The authors want to acknowledge the financial support from Prémios Santa Casa Neurociências ‐ Prize Melo e Castro for Spinal Cord Injury Research (MC-04/17); from Portuguese Foundation for Science and Technology [Doctoral fellowship (SFRH/BD/103075/2014) to EDG; Post‐ Doctoral fellowship (SFRH/BPD/97701/2013) to NAS; IF Development Grant to AJS]. This work is funded by national funds through FCT under the scope of grant reference TUBITAK/0007/2014 and 3599-PPCDT Project: PTDC/DTP-FTO/5109/2014. This article has been developed under the scope of the projects NORTE-01-0145- FEDER-000013, supported by the Northern Portugal Regional Operational Programme (NORTE 2020), under the Portugal 2020 Partnership Agreement, through the European Regional Development Fund (FEDER). This work has been funded by FEDER funds, through the Competitiveness Factors Operational Programme (COMPETE), and by National funds, through the Foundation for Science and Technology (FCT), under the scope of the project POCI-01- 0145-FEDER-007038.